SCIENTIFIC JUSTIFICATION OF THE USE OF CONE-BEAM COMPUTERIZED TOMOGRAPHY (CBCT) FOR CEPHALOMETRIC ANALYSIS IN THE «AUDAXCEPH» PROGRAMM - V.D. Kuroiedova; Y.Y. Vyzhenko; O.M. Makarova; O.A. Stasiuk (Ukrainian Medical Stomatological Academy, 2019)
This article is concerned with peculiarities of points' placement in orthodontics and study of cephalometric parameters on 3D reconstructions. The aim of the investigation is to develop out the algorithm of distribution of main cephalometric points on 3D reconstructions, received from CBCT and compare characteristics of measurements done on classic teleroentgenogram (TRG) and 3D reconstructions. Materials and methods. The main angular (SNA, SNB, ANB, SN-Ba) skeletal saggital parameters, vertical (ML-NSL, NL-ML, Facial axis, <G), and dental were taken (+1/NL, -1/ML, +1/-1). The analysis of dental radiographs was done for cephalometry «AudaxCeph». Teleroentgenogram and 3 D reconstructions of 20 patients were investigated. Comparing all indices of TRG and 3D reconstructions statistically significant difference was not revealed (р> 0,05). The most significant indices was established during the study of incisive indices - +1/NL, 110±2,72 и 110,2±5,02 correspondingly inter-incisal angle +1/-1 - 133,8±2,21 and 138±5,79.